Isolation and Characterization of Potassium-Solubilizing Bacteria from Two Different Rhizospheres and a Cow Manure in IPB University - Dori Kusuma Jaya; Sari Yulia Kartika Hasibuan; Deseriana Bria (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Applying PGPB (Plant Growth-Promoting Bacteria) as bioinoculant under the excessive and continuous use of chemical fertilizer, pesticide, and herbicide need to be highlighted nowadays. One of the most beneficial PGPB is potassium-solubilizing rhizobacteria. Potassium is one of the elements that plant absorbs in a large amounts along with nitrogen. Soil in various regions of Indonesia have low potassium solubility. Therefore, finding the best novel isolates contributing to potassium solubilization need to be carried out continually. The aim of this study is to find potassium-solubilizing bacteria from two different rhizospheres (banana and chili plant) in Leuwikopo Experimental Garden and a cow manure in Cattle Pen, IPB University. To obtain the potassium-solubilizing isolates, we observed and characterized the best growing isolates and measured the solubilizing zone on Alexandrov agar medium. Three out of 10 isolates were selected and tested their pathogenicity on tobacco leave. Solubilization index of three isolates from the highest to the lowest were MPK P (3.07), MPK KT (3.03), and MPK C (2.63), respectively. Necrotic on tobacco leave after isolates treatment showed negative result which means that the three isolates were not pathogenic to plant host. The isolates are recommended to be used as bioinoculant both in greenhouse and field plants which lack of potassium availability in soil.